Osthole: A Coumarin Derivative Assuage Thiram-Induced Tibial Dyschondroplasia by Regulating BMP-2 and RUNX-2 Expressions in Chickens - Muhammad Waqas; Yaping Wang; Aoyun Li; Hammad Qamar; Wangyuan Yao; Xiaole Tong; Jialu Zhang; Mudassar Iqbal; Khalid Mehmood; Jiakui Li (MDPI AG, 2019)
Avian tibial dyschondroplasia affects fast growing broiler chickens accounting for almost 30% of leg ailments in broilers. The present project was designed to assess the efficacy of osthole against avian tibial dyschondroplasia (TD). Two hundred and forty chickens were equally allocated into control, TD and osthole groups (n = 80). The TD and osthole group chickens were challenged with tetramethylthiuram disulfide (thiram) at 50 mg/kg of feed from 4−7 days, followed by osthole administration at 20 mg/kg orally to the osthole group only from 8−18 days. Thiram feeding resulted in lameness, increased mortality, and decreased production parameters, alkaline phosphatase (ALP), superoxide dismutase (SOD), total antioxidant capacity (T-AOC), and glutathione peroxidase (GSH-PX) levels, along with significantly increased aspartate aminotransferase (AST), alanine aminotransferase (ALT), malondialdehyde (MDA) levels, and growth plate size. Moreover, the genes and protein expressions of BMP-2 and RUNX-2 were significantly down-regulated in TD affected chickens (p < 0.05). Osthole administration showed promising results by alleviating lameness; increased ALP, SOD, T-AOC, and GSH-Px levels; and decreased the AST, ALT, and MDA levels significantly. It restored the size of the growth plate and significantly up-regulated the BMP-2 and RUNX-2 expressions (p < 0.05). In conclusion, the oxidative stress and growth plate anomalies could be assuaged using osthole.